UJI PERTUMBUHAN DAN HASIL BEBERAPA GENOTIPE TANAMAN TOMAT (Lycopersicum esculentum Mill) DI DATARAN RENDAH - Magdalena, Lia; Zuhry, Elza; ', Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Tomatoes as one of vegetables has a bright prospect. Low productivity of tomato caused by low soil fertility, pests and diseases. This study aims to determine the growth and yield of tomato plants with multiple strains Intan and Karina in the lowlands. This study using a completely randomized block design (CRBD) consisting of 6 treatments and 3 replications, so there are 18 experimental units. The treatments were: genotype IPB T60-2-6, IPB T64-2-2(1), IPB T3- 8-, IPB T53-3-3, Intan variety and Karina. The genotypes treatments were significantly affect the days to flowering, harvesting time, plant height, stem diameter, fruit length, fruit diameter, number of fruit cavities, fruit flesh thickness, number of seeds per gram, weight per fruit, and total weight per plant. Genotype T3-8-10 has growth and high yields compared of genotype IPB T64-2-2(1), IPB T60-2-6, IPB T53-3-3, Intan variety and Karina. Keywords : Lycopersicum esculentum, lowlands, genotypes